2024
DOI: 10.2174/1386207325666220707113100
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Prognostic Values of COL4As Transcriptional Expressions in Clear Cell Renal Cell Carcinoma Patients

Abstract: Objective: The COL4A family genes (COL4As) are a set of extracellular matrix-related genes that have been proved a tight relationship among various cancers. However, the functional role of different COL4As (COL4A1/2/3/4/5/6) in clear cell renal cell carcinoma (ccRCC) is unclear. Methods: We obtained the data from online open-access databases including ONCOMINE, UALCAN, GEPIA, Cancer Genome Atlas (TCGA), cBioPortal, METASCAPE, STRING, TIMER, GSCALite, MEXPRESS, and TISIDB to explore the correlation between CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Knockdown of COL4A3 significantly increased the invasion and migration ability of nasopharyngeal carcinoma cancer cells [26]. The diminished expression of COL4A4 is associated with poorer prognosis, while the downregulation of COL4A6 promotes prostate cancer progression and invasion [15,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of COL4A3 significantly increased the invasion and migration ability of nasopharyngeal carcinoma cancer cells [26]. The diminished expression of COL4A4 is associated with poorer prognosis, while the downregulation of COL4A6 promotes prostate cancer progression and invasion [15,27].…”
Section: Discussionmentioning
confidence: 99%
“…The COL4 family, consisting of six genes-COL4A1, COL4A2, COL4A3, COL4A4, COL4A5, and COL4A6, is a group of subtypes in the COL family. Tu et al discovered that clear cell renal cell carcinoma (ccRCC) tissue exhibited significantly diminished expression of COL4A3/4/5/6 in comparison to normal renal tissue, while showing markedly elevated expression of COL4A1/2 [15]. Patients with negative COL4A2 and COL4A6 in extrahepatic bile duct cancer exhibited notably poorer prognoses than those with positive COL4A2 and COL4A6 [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that deletion of COL15A1 modulates the tumor ECM and leads to increased tumor growth in the mouse mammary carcinoma model [ 29 ]. The transcript levels of COL4A4 and 6 could act as potential indicators for early disease progression in ccRCC [ 30 ]. Yongcan et al defined that DCN deficiency promotes RCC growth and metastasis through the downregulation of P21 and E-cadherin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…recently reported that the HMCN1 mutations are frequently detected in patients with ccRCC and are correlated with a higher tumor mutation burden and dismal clinical consequences, and may correlate with anti-tumor immunity and cell metabolism ( 42 ). In addition, COL4A4 has been identified as an unfavorable prognostic factor for ccRCC ( 43 ). The functions of other genes in ccRCC currently remain unknown and require further exploration.…”
Section: Discussionmentioning
confidence: 99%